Left ventricular structure and function in reproductive-aged female patients with rheumatoid arthritis - Svetlana Anatolyevna Polyakova; T A Raskina (Современная ревматология, 2013)
In patients with rheumatoid arthritis (RA), the signs of left ventricular diastolic dysfunction and hypertrophy are detectable just at the preclinical stage of myocardial damage. RA activity, rheumatoid factor seropositivity, and systemic manifestations of the disease should be considered to be risk factors of early cardiac involvement.